First report on the seroprevalence of avian encephalomyelitis virus antibody in Sonali (cross-bred) chickens in Bogura, Bangladesh - Ali, Md Zulfekar; Shaon, Md Taohid Wasim; Moula, Mohammad Moktader; Bary, Md Akramul; Sabuj, Abdullah Al Momen; Khaled, Shamsul Arefin; Bhuiyan, Zafar Ahmed; Giasuddin, Md (Journal of Advanced Veterinary and Animal Research, 2021)
Objectives: The study intended to detect the presence and distribution of avian encephalomyelitis virus (AEV)-specific antibodies in Sonali (cross-bred) parent chickens regarding farm location, flock size, and age in Bogura district of Bangladesh, a Sonali chicken belt. Materials and methods: A total of 275 Sonali parent chickens’ blood samples were collected randomly from 39 flocks during laying age with a healthy and non-vaccination history against AEV. Blood samples were collected aseptically from the wing veins of chickens using 3-ml syringes and sera were separated. Then, the sera were transferred to the laboratory by maintaining a cool chain. Indirect enzyme-linked immunosorbent assay was used to detect the specific antibodies against AEV present in the sera samples. Results: Overall, 70.18% of the chickens were found seropositive for AEV antibodies. Based on the location, the highest seropositivity was recorded in Bogura Sadar [91.30%, confidence intervals (CI) 79.21%–97.58%], and the lowest was in the Adomdighi sub-district (45.45%, CI 29.49%– 63.08%). For flock size, AEV seropositivity was significantly (p < 0.05) higher in the large flock (82.22%, CI 72.74%–89.48%). Regarding age groups, the seropositivity of AEV was significantly (p < 0.05) increased with chickens’ age. Higher seropositivity was noted in chickens aged >51 weeks (89.32%, CI 81.69%–94.55%). Conclusion: The results indicate that AEV is circulating in the environment, and chickens were exposed to the field strain of AEV. To the best of our knowledge, this is the first report on AEV in chickens in Bangladesh. Proper vaccination and standard farm biosecurity practice could minimize AEV infection in chickens. A detailed epidemiology study, detection, and characterization of the AEV would be essential for effective AEV infection control. J. Adv. Vet. Anim. Res., 8(1): 78-83, Mar 2021 http://doi.org/10.5455/javar.2021.h488